Assessing the cross-sectional and inter-temporal validity of the Household Food Insecurity Access Scale (HFIAS) in Burundi - Desiere, Sam; D’Haese, Marijke; Niragira, Sanctus (Public health nutrition, 2015)
To examine the cross-sectional and inter-temporal validity of the Household Food Insecurity Access Scale (HFIAS) for rural households in Burundi. Longitudinal survey about food security and agricultural production, individually administered by trained interviewers in June 2007 and 2012. Ngozi, north of Burundi. Three hundred and fourteen household heads were interviewed. Tobit models showed that the HFIAS was significantly correlated with objective measures of food security, in this case total annual food production (P<0·01), livestock keeping (P<0·01) and coffee production (P<0·01) in both 2007 and 2012. This confirms that the HFIAS is cross-sectionally valid and corroborates the findings of previous studies. However, while total food production decreased by more than 25 % in terms of energy between 2007 and 2012, households reported an improvement in their perceived food security over the same period, with the HFIAS decreasing from 13·9 to 10·8 (P<0·001). This finding questions the inter-temporal validity of the HFIAS. It may be partly explained through response shifts, in which households assess their own food security status in comparison to that of their peers. The evidence from our study suggests that the HFIAS is cross-sectionally valid, but may not be inter-temporally valid, and should not be used as a single indicator to study temporal trends in food security.